Respuesta :

Answer:

X = -1/3, 1/3

Step-by-step explanation:

6x^2 - x = 1

(subtract 1 from both sides)

6x^2 - x - 1 = 0

(factor)

(6x - 3) (6x + 2)

(simplify)

(2x - 1) (3x + 1)

(Solve for x in each parentheses)

2x-1= 0 and 3x+1=0

X= -1/2 X= -1/3

Answer:

x=-1/2,-1/3

Step-by-step explanation:

6x²-x = 1 <- Rewrite

       -1  -1 <- Subtract 1 from both sides

6x²-x-1 = 0

x²-x-6 = 0 <- Slide the x²'s coefficient over to the variable with no coefficient through multiplication

(x-3)(x+2)=0 <- Factor

(x-3/6)(x+2/6)=0 <- Divide the 6 back out and simplify

(x-1/2)(x+1/3)=0 <- Simplify

(2x-1)(3x+1)=0 <Bring the denominator in front of the x

2x+1 = 0 and 3x+1 = 0 <- Seperate the two and solve

    -1    -1             -1    -1

  2x = -1 and      3x = -1

   x = -1/2 and      x = -1/3

so

x=-1/2,-1/3